Investigation of non-rectangular RF pulse influence in emitted electron beam of the thermionic rf-gun at the linac-based THZ facilty in Thailand - Damminsek K. (2015)
An electron gun of a linac-based THz radiation source at the Plasma and Beam Physics (PBP) Research Facility at Chiang Mai University (CMU) in Thailand is a 1-1/2 cell S-band standing wave RF cavity with an Os/Ru coating tungsten dispenser cathode. The electron current density of a few A/cm2 can be achieved from zero-field thermionic emission using this cathode type at a desired operating temperature. However, non-rectangular RF pulse shape has a significant influence on the acceleration of electrons inside the RF cavity, which leads to the properties of the output electron beam from a thermionic RF-gun. Numerical and experimental studies on the contribution of the effect have been carried out. Results of the investigations are presented and discussed in this contribution. Copyright © 2012 by the respective authors.